Model Of Punishment: Juvenile Justice Systems - Nur, Rafika; Bakhtiar, Handar Subhandi; Miqat, Nurul; Darmawati, Darmawati; Mustawa, Mustawa (Jambura Law Review, 2021)
The position of children who have special rights in the law makes children get special treatment. In the juvenile justice system in Indonesia, there are two systems of sanctions, namely criminal sanctions and actions, and this is done to realize the protection of children who are dealing with the law.  This research is a normative juridical review, using a statute, comparative and conceptual approaches. The results show that the imposition of sanctions on children is based on the child's age, where children aged 12 to before 14 years can only be sanctioned with actions, and children aged 14 to before 18 years may be subject to criminal sanctions or actions.